NSAID use may decrease serum Klotho levels - Yan, Jingchao; Sun, Hong; Xin, Xiu; Huang, Taomin (Frontiers in Endocrinology, 2025)
ObjectiveTo validate the hypothesis proposed by previous studies, which suggests that NSAID use may elevate Klotho levels.MethodWe conducted a cross-sectional study involving 11,626 adults from the National Health and Nutrition Examination Survey (NHANES) 2007-2016. Multivariable linear regression and propensity score analysis were employed to evaluate the association between NSAID use and serum Klotho levels. Additionally, subgroup analyses were performed to assess the consistency of this relationship across various subgroups.ResultsMultivariable linear regression analysis demonstrated that NSAID use was negatively correlated with serum Klotho levels (β = -25.48 [95% CI: -42.00, -8.96], p = 0.003). Additionally, sensitivity analysis results were consistent with the primary analysis. Subgroup analyses did not reveal any statistically significant interactions.ConclusionContrary to previous speculations, the use of NSAIDs is associated with a decrease in serum Klotho levels.